A Correlation Between Leg Muscle Explosive Power And Ankles Coordination On The Shooting Accuracy In Soccer Games In Sukasari Village Club - Putu Krisna Aditya; Juwita Juwita; Supriyanto Supriyanto (Perkumpulan Dosen Muda Bengkulu, 2021)
The purpose of this study is to determine the correlation between the explosive power of the leg muscles and the coordination of the ankles on the accuracy of shooting in soccer games in Sukasari Village club. The method used in this research is correlational quantitative method. The population in this study were 20 athletes in Sukasari Village, while the sample in this study were 20 athletes (all). The instruments in this study were the Standing Long Jump test, the Mitcel Soccer test, and the At The Ball shooting test. The data analysis requirements used were the Lillifors normality test and the homogeneity test. The data analysis used was the product moment correlation analysis with a significance level of 5%. Based on the results of the study, it was found that there was a significant relationship between the explosive power of the leg muscles and the coordination of the ankles (X) on the shooting accuracy as indicated by rx1x2y = 0.920 r (0.5) (20) = 0.444.